CATALYSTS OF CHANGE: EXPLORING THE TRANSFORMATIVE IMPACT OF TECHNOLOGY AND VISUAL AIDS LIKE PROJECTORS ON MODERN EDUCATION - Amina Bibi; Dr. Sumera Mehmood; Abida Bibi (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the effectiveness of utilizing technology and visual aids, such as images, animated videos, projectors, and films, as motivational tools to enhance students’ attention during the reading of literary texts. Conducted in educational institutions within District Chakwal Teh Lawa, data collection was carried out through a test both public and private school students. Employing primary data collection methods, the study included all girls’ high school students from Tehsil Lawa, with 8th-grade students from Muhammadan public girls’ high school selected as the sample from the population. The students were divided into two groups, control and experimental, based on their pre-test scores, utilizing convenience sampling. The control group received traditional instruction through lecture methods, while the experimental group underwent conceptual learning using the technology like visual aids and projectors. Data collection involved pre-tests and post-tests, and the analysis utilized statistical measures such as mean, S.D and t test the study utilized SPSS software for data analysis, with findings presented through pie, and bar graphs. Results indicate a predominantly positive perception among teachers and students regarding the benefits of incorporating visual aids in the learning process.